Rozvoj infrastruktury komunálního podnikání v kontextu externího zajišťování komunálních služeb (Development of Infrastructure of the Municipal Enterpreneurship in the Context of the Outsourced Providing for Municipal Services) - Karel Lacina; Hana Matoušková (DETUROPE)
The aim of the paper is to discuss the situation of the municipal enterpreneurship in some EU member countries (namely Great Britain, France, Germany, Austria and Scandinavian countries) with regards to the process of privatization running out since later 1970s and the subsequent outsourcing of contracting the municipal service provision by private companies. This situation was related to the shortage within public budgets as well to the influence of the so called New Public Management ideas. The findings are compared with the situation in the Czech Republic. The fully privatized sector of municipal services did not show to be the best way of how to provide citizens with such services. The procurement of public services for individual settlements proved to be quite successful by means of collective communal enterprises or through the joint contracting of these services by a group of municipalities with the private entities in Western countries. Unfortunately such a co-operation does not find place in the Czech Republic.